MEMBUAT DESAIN PACKAGING PRODUK BODY CARE REVEUSE - Michelle Caroline Kristanto (Jurnal Vicidi, 2021)
In increasing self-confidence in appearance, it is necessary to maintain a clean and healthy body by exfoliating the skin. Reveuse comes with a beauty product in the form of a natural body scrub cube that can treat skin efficiently and can increase the confidence of women aged 18 to 29 who love skincare. In an effort to solve these problems, Reveuse faces a problem in making a suitable design for the packaging of Reveuse body scrub products because the product being offered is a body scrub cube which is still not well known and recognized by the public. Therefore, the problem formulation of this journal is how to make packaging design for Reveuse body care products. The purpose of designing this final project is to create a packaging design for Reveuse body care products so that the product is easier to recognize as a beauty product and has its own charm. The research methods used were qualitative and quantitative through literature studies, interviews with three expert users, three extreme users, and a survey to 100 target audiences. Based on the results of a trial analysis of Reveuse's packaging design work, several designs will be revised, namely the use of Reveuse's main typeface and designs for packaging pouches that don't look like skincare products. Keywords: Body Care, Packaging, Design Style, Color Palette, Typography